2017
DOI: 10.2136/vzj2017.02.0047
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Transfer of Organic Carbon and Phosphorus by Water Erosion at Hillslope Scale in Southern Spain Olive Orchards

Abstract: Core Ideas A 3‐yr hillslope study presents DOC, DOC, TP, and DRP losses from several olive orchards. Losses of DOC and TOC were higher than those measured in other agricultural systems. Losses of TP were at the high‐end range of losses measured in agricultural systems. Temporary cover crops in lanes can reduce TOC and TP losses through reduced sediment losses. Cover crops did not significantly reduce DOC and DRP in runoff compared with conventional tillage. Dissolved organic C (DOC) and dissolved reactive P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…7.8 kg DOC ha −1 yr −1 ) and lower than the losses of total organic carbon (ca. 101 kg TOC ha −1 yr −1 ) measured by Gómez et al [46] in Spanish olive orchard plots with CC. Besides, these authors also reported clear benefits on reducing the loss of carbon in those plots with CC compared with the plots under CT.…”
Section: Organic Matter Content In the Sediment Samplesmentioning
confidence: 94%
“…7.8 kg DOC ha −1 yr −1 ) and lower than the losses of total organic carbon (ca. 101 kg TOC ha −1 yr −1 ) measured by Gómez et al [46] in Spanish olive orchard plots with CC. Besides, these authors also reported clear benefits on reducing the loss of carbon in those plots with CC compared with the plots under CT.…”
Section: Organic Matter Content In the Sediment Samplesmentioning
confidence: 94%
“…In farmland with annual crops, conservation tillage (reduced/no-tillage with/out residues) is beneficial to the improvement of integrated soil fertility and crop yield [21]. In permanent crops (e.g., vineyards, olive groves and other fruit-tree orchards), the use of ground covers (e.g., spontaneous vegetation, seeded permanent/temporary cover crop (CC), mulching and agro-textile) has demonstrated its effectiveness to reduce runoff yield, increase surface water infiltration [22] and minimize the loss of soil [23], soil organic matter [13], soil organic carbon [14] and nutrients [24].…”
Section: Sustainability By Functionmentioning
confidence: 99%
“…Expansion of the drainage network and development of gullies Nyssen et al, 2004;Palacio Prieto and López Blanco, 1994;Vandekerckhove et al, 2001;Ries and Marzolff, 2003 Rise in agricultural costs Valentin et al, 2005;Santos Telles et al, 2011;Panagos et al, 2018 "Off site" effects Reference Silting-up of reservoirs and loss of functionality Poesen et al, 2002;de Vente et al, 2005;Haregeweyn et al, 2003;Valentin et al, 2005;Haregeweyn et al, 2008 Increment in floods Poesen and Hooke, 1997;Martineli Costa and Prado Bacellar, 2007;Obi Lawrence, 2017. Contamination of soils and surface waters Toy et al, 2002;Gómez et al, 2017;Issaka and Ashraf, 2017.…”
Section: Loss Of Agricultural Landmentioning
confidence: 99%